2010
DOI: 10.1002/art.27701
|View full text |Cite
|
Sign up to set email alerts
|

CD248 and its cytoplasmic domain: A therapeutic target for arthritis

Abstract: Objective. CD248 is a transmembrane glycoprotein expressed on the surface of activated perivascular and fibroblast-like cells. This study was undertaken to explore the function of CD248 and its cytoplasmic domain in arthritis.Methods. Synovial tissue biopsy samples from healthy controls, from patients with psoriatic arthritis (PsA), and from patients with rheumatoid arthritis (RA) were stained for CD248. Transgenic mice that were CD248-deficient (CD248-knockout [CD248 KO/KO ]) or mice with CD248 lacking the cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 48 publications
4
92
0
Order By: Relevance
“…However, expression is downregulated postnatally but upregulated during tissue remodeling. We found CD248-expressing fibroblasts predominantly in the sub-lining tissue of the inflammatory synovium, consistent with previous studies [32]. As expected from their anatomical location, CD248 + SF did not invade the implants of cartilage in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…However, expression is downregulated postnatally but upregulated during tissue remodeling. We found CD248-expressing fibroblasts predominantly in the sub-lining tissue of the inflammatory synovium, consistent with previous studies [32]. As expected from their anatomical location, CD248 + SF did not invade the implants of cartilage in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…42 In addition, it has been demonstrated recently that embryonic fibroblasts expressing endosialin with a truncated cytoplasmic domain are impaired in their ability to bind U937 monocytes. 43 Therefore, endosialin may also modulate selective vessel pruning via its ability to promote localized leukocyte recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…42 In addition, it has been demonstrated recently that embryonic fibroblasts expressing endosialin with a truncated cytoplasmic domain are impaired in their ability to bind U937 monocytes. 43 Therefore, endosialin may also modulate selective vessel pruning via its ability to promote localized leukocyte recruitment.Very little is known about the mechanisms by which particular vessels are selected for pruning while adjacent vessels remain patent. Our data presented herein demonstrate that endosialin plays a role in this process and further suggest that the activity of endosialin could be restricted to selected vessels by the regulated availability of its ligand.…”
mentioning
confidence: 99%
“…Indeed, using anti-IL-6 and anti-IL-1 receptor mABs, Kawane et al (28) were able to impede the "cytokine storm" and block joint swelling. Furthermore, Maia et al (29) used ArthroMAB to induce CAIA, and found that removing the cytoplasmic domain of CD248 impaired TNF-α-induced monocyte adhesion, underscoring the importance of regulating TNF-α production in rheumatoid arthritis. Recent clinical trials demonstrated that soluble tumor necrosis factor-receptor immunoglobulin fusion protein (TNFRIg) and anti-TNF-α antibodies can reduce synovitis and serum markers for inflammation.…”
Section: Discussionmentioning
confidence: 99%